Medialne reprezentacje kultury literackiej, czyli wiedza o książce dla dzieci – (nie) tylko w Sieci - Marta Krasuska-Betiuk (Problemy Wczesnej Edukacji)
The purpose of the text is to identify and description certain dimensions of literary culture that are represented in digital media and relate to the children’s recipient. The method used content analysis, mainly Polish websites, indicate the dominant media enabled representations of knowledge about children’s book and its contexts (reading culture, the role of intermediary). Described some forms of presence of literature for children and youth in cyberspace, such as portals and blog reviewers, websites writers and books, journals and literary blogs, forums readers, radio and TV programs. Scientific knowledge of literary culture is represented in the network to a lesser extent in comparison to popularizing, commercial and promotional activities of publishers and other entities. The source of scientific information are the pages of international conferences, associations, organizations and libraries. To a lesser degree, open source licenses are digitally released as original scientific studies, such as books, journals and research reports.